Negation in Near‐Native French: Variation and Sociolinguistic Competence. Issue 1 (3rd August 2016) - Donaldson, Bryan
Abstract : This study investigated how adult second language (L2) speakers of French with near‐native proficiency realize verbal negation, a well‐known sociolinguistic variable in contemporary spoken French. Data included 10 spontaneous informal conversations between near‐native speakers of French and native speakers (NSs) closely acquainted with them. Although some near‐native speakers retained ne more frequently than their interlocutors, others produced ne at rates indistinguishable from the NSs. A variationist analysis of 1, 877 examples of negation revealed that the near‐native speakers had largely acquired the relevant linguistic and sociostylistic factors that condition NS use, although an important subset of the near‐native speakers did not vary their ne use according to whether the negation appears in a lexicalized or nonlexicalized phrase. The results contribute to understanding L2 near‐nativeness, specifically with respect to sociolinguistic competence in adult learners.